Observation of a Gelatinous Octopod, Haliphron atlanticus, along the Southern West Mariana Ridge: A Unique Cephalopod of Continental Slope and Mesopelagic Communities. (20th May 2018) - Miller, Michael J.; Miwa, Tetsuya; Watanabe, Shun; Kuroki, Mari; Higuchi, Takatoshi; Takeuchi, Aya; Serizawa, Kenta; Okino, Tatsufumi; Tsukamoto, Katsumi
Abstract : The circumglobal deep-sea gelatinous giant octopod, Haliphron atlanticus, reaches 4 m in length and uses both benthic and pelagic habitats in the upper 3000 m of the ocean during different life history stages, but it is rarely observed due to the deep-depths where it typically lives. It has been collected in trawls and observed a few times near continental margins or islands and has been identified in the stomach contents of deep-diving predators such as sperm whales and blue sharks or detected as body fragments after predation events. An individual H. atlanticus ( 1 m in total length) was video-recorded at 12:21 for about 3 minutes in front of the Shinkai 6500 submersible at 586–599 m (6.5°C, salinity 34.4) along the West Mariana Ridge. It made no escape attempt as the submersible approached and it moved slowly up or down in front of the submersible. It was over the outer seamount-slope (bottom depth 3208 m) 50 km west of seamounts (≥1529 m summits), but how it fits into the mesopelagic food web along the ridge is unclear. More information is needed to understand the role of H. atlanticus in oceanic food webs and if it typically lives along seamount ridges.